Adventitious discovery of elastofibroma dorsi on skin biopsy - Salsabil Attafi Sehli; Mariem Bel Haj Salah; Ines Smichi; Wafa Koubaa; Olfa Khayat; Aschraf Chadli Debbiche (Our Dermatology Online, 2015)
Elastofibroma dorsi is a rare soft tissue pseudotumor, slow-growing, sitting in 99% of cases at the subscapular region and occurring in the elderly active people. Its pathogenesis is unclear. It is often asymptomatic. However, the diagnosis can be made on the typical topography of the mass and its characteristic appearance on CT and MRI. Thus, in the literature, most of the reported cases were radiologically discovered. An incidental histological discovery, like in our case is rare. We report the case of a 63 year-old man who had multiple nodular lesions, well circumscribed, firm, sometimes inflammatory, measuring between 3 and 5 cm, and located on the thighs and the paravertebral and scapular regions. The chest x-ray showed a right basal opacity suggesting a malignant processus. These nodules were biopsied in search of cutaneous metastasis of a probable pulmonary neoplasia. At histological examination, the diagnosis of elastofibroma was retained. Despite its rarity, the dorsal elastofibroma deserves to be known, thus avoiding excessive surgery. We propose to study its clinical, radiological and pathological features and its therapeutic modalities.